Family-specific aggregation of lipid GWAS variants confers the susceptibility to familial hypercholesterolemia in a large Austrian family. (September 2017) - Nikkola, Elina; Ko, Arthur; Alvarez, Marcus; Cantor, Rita M.; Garske, Kristina; Kim, Elliot; Gee, Stephanie; Rodriguez, Alejandra; Muxel, Reinhard; Matikainen, Niina; Söderlund, Sanni; Motazacker, Mahdi M.; et al.
Abstract: Background and aims: Hypercholesterolemia confers susceptibility to cardiovascular disease (CVD). Both serum total cholesterol (TC) and LDL-cholesterol (LDL-C) exhibit a strong genetic component (heritability estimates 0.41–0.50). However, a large part of this heritability cannot be explained by the variants identified in recent extensive genome-wide association studies (GWAS) on lipids. Our aim was to find genetic causes leading to high LDL-C levels and ultimately CVD in a large Austrian family presenting with what appears to be autosomal dominant inheritance for familial hypercholesterolemia (FH). Methods: We utilized linkage analysis followed by whole-exome sequencing and genetic risk score analysis using an Austrian multi-generational family with various dyslipidemias, including elevated TC and LDL-C, and one family branch with elevated lipoprotein (a) (Lp(a)). Results: We did not find evidence for genome-wide significant linkage for LDL-C or apparent causative variants in the known FH genes rather, we discovered a particular family-specific combination of nine GWAS LDL-C SNPs ( p  = 0.02 by permutation), and putative less severe familial hypercholesterolemia mutations in the LDLR and APOB genes in a subset of the affected family members. Separately, high Lp(a) levels observed in one branch of the family were explained primarily by the LPA locus, including short (<23) Kringle IV repeats and rs3798220. Conclusions: Taken together, some forms of FH may be explained by family-specific combinations of LDL-C GWAS SNPs. Highlights: We systematically screened a large Austrian family for monogenic and polygenic causes of familial hypercholesterolemia (FH). Family-specific LDL-C GWAS variants and an aggregate of milder mutations in APOB and LDLR may explain some forms of FH. Short Kringle IV repeats and SNP rs3798220 at the LPA locus likely explain high Lp(a) levels in one branch of the family.